PENGEMBANGAN BOOKLET BERBASIS PODE (PREDICT,OBSERVE, DISCUSS,EXPLAIN) UNTUK MENINGKATKAN BERPIKIR KRITIS PADA MATERI IPA KELAS IV SDN TOYORESMI - Wahyuningtyas, Putri; Zainuddin; Aynin Mashfufah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Education in Indonesia prepares the next generation of quality and skills. One of the skills that students must have in the 21st century is critical thinking. The development of PODE-based booklets is considered important to improve students' critical thinking at school. This study aims to test the feasibility of the booklet produced as teaching materials in elementary schools and determine its effectiveness in improving students' critical thinking. This research uses the ADDIE model (Analzye, Design, Development, Implementation, Evaluation). This research was conducted at SDN Toyoresmi, Ngasem District, Kediri with research subjects in the form of material expert validators, teaching material experts, teachers and 36 fourth grade students. Data collection techniques are observation, interviews, questionnaires, and tests. The instruments used are questionnaires given by teaching material experts, material experts, grade IV teachers in elementary schools and test questions given 10 pre-test and post-test questions. The results of the validity test by material experts 98.2% and teaching material experts 83.3%. The practicality test results were 90.2% in the very practical category. Furthermore, the average pre-test effectiveness test results obtained 47 and the average post test 87. So it can be concluded that the post test results have increased. Based on the research findings, PODE-based booklets can improve critical thinking skills so that they are suitable for use as teaching materials in grade IV elementary schools.